Leadership in Literacy: The Role of Instructional Leadership in Fostering Student Reading Achievement - Andrin, Glenn; Kilag, Osias Kit; Abella, Julanie; Tañiza, Frolomea Narra; Groenewald, Elma; Cordova Jr., Nelson (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2024)
This study investigates the intricate interplay between leadership practices and the outcomes of literacy interventions in educational settings. Drawing from an integrative literature review methodology, the research synthesizes insights from key studies to unravel the nuanced dynamics that shape successful literacy initiatives. Key findings highlight the pivotal role of leadership in designing and implementing effective literacy interventions. Leaders who strategically allocate resources, prioritize ongoing professional development, and embody transformational principles emerge as architects of change, fostering environments conducive to literacy success. However, the study also brings to light challenges faced by educational leaders in aligning practices with literacy intervention goals. Balancing competing priorities, managing resistance to change, and addressing resource constraints emerge as common obstacles, urging leaders to navigate these challenges strategically. This study advocates for a holistic approach to educational leadership, emphasizing the transformative power of leaders in shaping literacy excellence. By recognizing challenges, embracing innovation, and prioritizing the enduring impact of literacy interventions, stakeholders can collectively foster environments where literacy becomes a journey of discovery and lifelong learning. This research serves as a clarion call for visionary leadership as the linchpin of literacy success in diverse educational landscapes.